New xenophobia - Khair, Tabish (Oxford University Press, 2016)
Xenophobia, the fear or dislike of strangers, can be seen throughout the course of history in the form of communal riots, racist attacks, religious hatred, and genocide. HinduMuslim riots in India, SinhaleseTamil tensions in Sri Lanka, ethnic cleansing in former Yugoslavia, purging of Shias and Sunnis in Iraq and Syria, skinheads attacking immigrants, and the Jewish holocaust in Europe are a few examples.